A composite oxide solid base catalyst and its preparation method and application
By using an Elosite support to support a composite oxide catalyst of nano nickel oxide and nano lanthanum oxide in biodiesel preparation, the problems of liquid catalyst separation and short service life of solid catalysts are solved, and biodiesel with high efficiency catalytic activity and long life are achieved preparation.
Patent Information
- Application Number
- CN202211577727.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-12-09
AI Technical Summary
In the preparation of existing biodiesel, liquid catalysts are difficult to separate and reuse, resulting in environmental pollution, and solid catalysts such as calcium oxide have short service life and insufficient catalytic activity and selectivity.
Using eloite as a support and supporting nano nickel oxide and nano lanthanum oxide as active components, a composite oxide solid base catalyst is prepared through a specific preparation method to improve catalytic activity and service life.
It achieves efficient catalytic activity and reaction yield, extends the service life of the catalyst, and is easy to recover and reuse, reducing production costs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biodiesel, and in particular relates to a composite oxide solid base catalyst and a preparation method and application thereof. Background Art
[0002] As the most representative renewable green energy, biodiesel is a non-toxic, biodegradable, sustainable renewable energy source and has received extensive attention. Biodiesel is usually synthesized from animal and vegetable oils, waste cooking oils, etc. and short-chain alcohols as raw materials, and its main component is fatty acid alkyl esters, such as fatty acid methyl esters.
[0003] The traditional method of preparing biodiesel is to use liquid catalysts through esterification or transesterification reactions. However, liquid catalysts are difficult to separate from biodiesel, are not easy to reuse, and will cause certain waste liquid emissions during the production process, leading to environmental pollution. At the same time, further purification of biodiesel will continue to increase the production cost of biodiesel. In order to improve the problems of liquid catalysts in terms of environmental pollution and recycling, solid catalysts have become a hot spot in current research and development. Calcium oxide is widely used as a solid base catalyst in the catalytic synthesis of biodiesel because of its low cost, easy availability and high catalytic activity; however, calcium oxide also has defects such as easy leaching of active sites, poor water and acid resistance, and poor service life during the catalytic synthesis of biodiesel.
[0004] Therefore, it is of great significance to develop a new solid base catalyst for biodiesel preparation to improve the catalyst activity, selectivity and service life. Summary of the invention
[0005] In order to overcome the deficiencies of the prior art, the present invention provides a composite oxide solid base catalyst and a preparation method thereof and application thereof in the preparation of biodiesel.
[0006] The first object of the present invention is to provide a composite oxide solid base catalyst, wherein the solid base catalyst uses halloysite as a carrier to load active components; the active components include nano nickel oxide and nano lanthanum oxide.
[0007] The present invention is further configured such that the mass ratio of the carrier halloysite to the active component is 1:(0.5-1), wherein the mass ratio of nano nickel oxide to nano lanthanum oxide is 1:(0.1-0.5), preferably 1:(0.3-0.5).
[0008] The present invention is further configured such that the particle size of the active component nano nickel oxide is 10 to 30 nm, and the particle size of the nano lanthanum oxide is 50 to 100 nm.
[0009] The second object of the present invention is to provide a method for preparing the composite oxide solid base catalyst, which specifically comprises the following steps:
[0010] (1) adding purified halloysite powder into water, stirring and mixing at room temperature to obtain a mixed solution A;
[0011] (2) mixing the nickel nitrate and lanthanum nitrate solutions uniformly to obtain a mixed solution B;
[0012] (3) adding the mixed solution B to the mixed solution A, stirring at 50-70° C. for 6-12 hours, so that the metal nickel ions and lanthanum ions are uniformly adsorbed in the pores of the halloysite powder, to obtain a mixed solution C;
[0013] (4) After the stirring is completed, the mixed solution C is centrifuged and dried, and the obtained product is calcined and activated to obtain a solid base catalyst loaded with nickel oxide and lanthanum oxide.
[0014] The present invention is further configured that, in the step (1), the halloysite is ground and sieved to 200 mesh to obtain the halloysite powder; and the step of purifying the halloysite powder comprises:
[0015] The halloysite powder is immersed in a 0.5-1 mol / L dilute nitric acid solution, the mixing ratio of the halloysite powder and the dilute nitric acid solution is 30-80 g / L, and mixed at 60-90° C. for 6-12 hours, filtered, washed, dried, and calcined at 350-450° C. for 2-5 hours to obtain purified halloysite powder.
[0016] The present invention is further configured as follows: in the step (1), the purified halloysite powder is added to water and stirred at 300 to 400 r / min for 2 to 4 hours to obtain a mixed solution A; in the step (2), the solutions of nickel nitrate and lanthanum nitrate are mixed and ultrasonically dispersed for 10 to 20 minutes to obtain a mixed solution B.
[0017] The present invention is further configured such that, in step (3), the stirring speed of adding the mixed liquid B into the mixed liquid A is 350 to 450 r / min.
[0018] The present invention is further configured such that in the step (4), the product obtained after separation and drying is activated by calcining at 650-850° C. for 2-5 h in a muffle furnace to obtain the composite oxide solid base catalyst.
[0019] The third object of the present invention is to provide the use of the above-mentioned nano nickel oxide solid base catalyst in the preparation of biodiesel, which specifically comprises the following steps:
[0020] (1) Adding raw oil and methanol in a mass ratio of 1:(7-9) into a reaction kettle, stirring and heating to 70-90°C;
[0021] (2) Add the solid base catalyst into the reaction kettle, the mass ratio of the solid base catalyst to the raw oil is 2% to 3%, and react for 4 to 6 hours to prepare biodiesel.
[0022] The beneficial effects of the present invention are:
[0023] (1) The solid base catalyst of the composite oxide provided by the present invention uses nano nickel oxide and nano lanthanum oxide as active components. Both nano nickel oxide and nano lanthanum oxide are alkaline sites of the catalyst, and the addition of a certain amount of lanthanum oxide avoids the agglomeration of nano nickel oxide to a certain extent, making the distribution of active sites more uniform. The particle sizes are in the range of 10 to 30 nm and 50 to 100 nm, respectively, with good catalytic activity and high reaction yield. Halloysite is used as a catalyst carrier, and its spiral tubular well-developed pore structure is utilized to make the active components not easy to fall off and leach after being loaded, and the mass transfer resistance in the biodiesel reaction process is reduced, thereby improving the reaction efficiency.
[0024] (2) The solid base catalyst of the composite oxide is easy to recover and reuse, and can still maintain strong catalytic activity after repeated use, and has a long catalytic life.
[0025] (2) The preparation method of the solid base catalyst of the composite oxide is simple, the raw materials are readily available, and it is easy to apply industrially. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with examples. It should be understood that the following examples are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by professionals and technicians in this field based on the content of the present invention still belong to the scope of protection of the present invention.
[0027] Example 1
[0028] (1) Grinding and sieving halloysite to 200 mesh to obtain halloysite powder, immersing the halloysite powder in a 0.5 mol / L dilute nitric acid solution, the mixing ratio of the halloysite powder and the dilute nitric acid solution being 50 g / L, and mixing them uniformly at 60° C. for 10 h, filtering, washing, drying, and calcining at 350° C. for 4 h to obtain purified halloysite;
[0029] 1 g of purified halloysite powder was added into 200 mL of deionized water, and the mixture was stirred at room temperature and stirred at 300 r / min for 3 h to obtain a mixed solution A;
[0030] (2) 1.76 g of nickel nitrate hexahydrate and 0.13 g of lanthanum nitrate hexahydrate were added to 10 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed solution B;
[0031] (3) Adding mixed solution B to mixed solution A, stirring at 50° C. and 350 r / min for 12 h to obtain mixed solution C;
[0032] (4) After stirring, the mixed solution C is centrifuged and dried, and the obtained product is calcined in a muffle furnace at 650° C. for 5 h to obtain a solid base catalyst loaded with nickel oxide and lanthanum oxide.
[0033] The mass ratio of the carrier halloysite to the active component in the catalyst is 1:0.5, and the mass ratio of nickel oxide to lanthanum oxide in the active component is 1:0.1; it is detected that the particle size range of the nickel oxide loaded on the carrier is 10-50nm, and the particle size range of the lanthanum oxide is 50-150nm.
[0034] Example 2
[0035] (1) Grinding and sieving halloysite to 200 mesh to obtain halloysite powder, immersing the halloysite powder in a 0.5 mol / L dilute nitric acid solution, the mixing ratio of the halloysite powder and the dilute nitric acid solution being 80 g / L, and mixing them uniformly at 60° C. for 10 h, filtering, washing, drying, and calcining at 350° C. for 5 h to obtain purified halloysite;
[0036] 1 g of purified halloysite powder was added into 200 mL of deionized water, and the mixture was stirred at room temperature and stirred at 300 r / min for 3 h to obtain a mixed solution A;
[0037] (2) 1.29 g of nickel nitrate hexahydrate and 0.45 g of lanthanum nitrate hexahydrate were added to 10 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed solution B;
[0038] (3) Adding mixed solution B to mixed solution A, stirring at 60° C. and 450 r / min for 6 h to obtain mixed solution C;
[0039] (4) After stirring, the mixed solution C is centrifuged and dried, and the obtained product is calcined in a muffle furnace at 750° C. for 3 h to obtain a solid base catalyst loaded with nickel oxide and lanthanum oxide.
[0040] The mass ratio of the carrier halloysite to the active component in the catalyst is 1:0.5, and the mass ratio of nickel oxide to lanthanum oxide in the active component is 1:0.5; it is detected that the particle size range of the nickel oxide loaded on the carrier is 10 to 30 nm, and the particle size range of the lanthanum oxide is 50 to 100 nm.
[0041] Example 3
[0042] (1) Grinding and sieving halloysite to 200 mesh to obtain halloysite powder, immersing the halloysite powder in a 1 mol / L dilute nitric acid solution, the mixing ratio of the halloysite powder and the dilute nitric acid solution being 30 g / L, and mixing them uniformly at 80° C. for 6 h, filtering, washing, drying, and calcining at 400° C. for 2 h to obtain purified halloysite;
[0043] 1 g of purified halloysite powder was added into 200 mL of deionized water, stirred at room temperature, and stirred at 400 r / min for 2 h to obtain a mixed solution A;
[0044] (2) 3.00 g of nickel nitrate hexahydrate and 0.61 g of lanthanum nitrate hexahydrate were added to 10 mL of deionized water and ultrasonically dispersed for 20 min to obtain a mixed solution B;
[0045] (3) Adding mixed solution B to mixed solution A, stirring at 70°C and 400 r / min for 10 h to obtain mixed solution C;
[0046] (4) After stirring, the mixed solution C is centrifuged and dried, and the obtained product is calcined in a muffle furnace at 850° C. for 2 h to obtain a solid base catalyst loaded with nickel oxide and lanthanum oxide.
[0047] The mass ratio of the carrier halloysite to the active component in the catalyst is 1:1, and the mass ratio of nickel oxide to lanthanum oxide in the active component is 1:0.3; it is detected that the particle size range of the nickel oxide loaded on the carrier is 10-30nm, and the particle size range of the lanthanum oxide is 50-100nm.
[0048] Example 4
[0049] (1) Grinding and sieving halloysite to 200 mesh to obtain halloysite powder, immersing the halloysite powder in a 1 mol / L dilute nitric acid solution, the mixing ratio of the halloysite powder and the dilute nitric acid solution being 30 g / L, and mixing them uniformly at 90° C. for 12 h, filtering, washing, drying, and calcining at 450° C. for 2 h to obtain purified halloysite;
[0050] 1 g of purified halloysite powder was added into 200 mL of deionized water, and the mixture was stirred at room temperature and stirred at 400 r / min for 4 h to obtain a mixed solution A;
[0051] (2) 2.40 g of nickel nitrate hexahydrate and 0.50 g of lanthanum nitrate hexahydrate were added into 10 mL of deionized water and ultrasonically dispersed for 20 min to obtain a mixed solution B;
[0052] (3) Adding mixed solution B to mixed solution A, stirring at 50° C. and 400 r / min for 6 h, to obtain mixed solution C;
[0053] (4) After stirring, the mixed solution C is centrifuged and dried, and the obtained product is calcined in a muffle furnace at 850° C. for 2 h to obtain a solid base catalyst loaded with nickel oxide and lanthanum oxide.
[0054] The mass ratio of the carrier halloysite to the active component in the catalyst is 1:0.8, and the mass ratio of nickel oxide to lanthanum oxide in the active component is 1:0.3; it is detected that the particle size range of the nickel oxide loaded on the carrier is 10-30 nm, and the particle size range of the lanthanum oxide is 50-100 nm.
[0055] Example 5
[0056] (1) Grinding and sieving halloysite to 200 mesh to obtain halloysite powder, immersing the halloysite powder in a 0.5 mol / L dilute nitric acid solution, the mixing ratio of the halloysite powder and the dilute nitric acid solution being 50 g / L, and mixing them uniformly at 60° C. for 10 h, filtering, washing, drying, and calcining at 350° C. for 4 h to obtain purified halloysite;
[0057] 1 g of purified halloysite powder was added into 200 mL of deionized water, and the mixture was stirred at room temperature and stirred at 300 r / min for 3 h to obtain a mixed solution A;
[0058] (2) 1.29 g of nickel nitrate hexahydrate and 0.45 g of lanthanum nitrate hexahydrate were added to 10 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed solution B;
[0059] (3) Adding mixed solution B to mixed solution A, stirring at 50° C. and 350 r / min for 12 h to obtain mixed solution C;
[0060] (4) After stirring, the mixed solution C is centrifuged and dried, and the obtained product is calcined in a muffle furnace at 650° C. for 5 h to obtain a solid base catalyst loaded with nickel oxide and lanthanum oxide.
[0061] The mass ratio of the carrier halloysite to the active component in the catalyst is 1:0.5, and the mass ratio of nickel oxide to lanthanum oxide in the active component is 1:0.5; it is detected that the particle size range of the nickel oxide loaded on the carrier is 10 to 30 nm, and the particle size range of the lanthanum oxide is 50 to 100 nm.
[0062] Example 6
[0063] (1) Grinding and sieving halloysite to 200 mesh to obtain halloysite powder, immersing the halloysite powder in a 0.5 mol / L dilute nitric acid solution, the mixing ratio of the halloysite powder and the dilute nitric acid solution being 50 g / L, and mixing them uniformly at 60° C. for 10 h, filtering, washing, drying, and calcining at 350° C. for 4 h to obtain purified halloysite;
[0064] 1 g of purified halloysite powder was added into 200 mL of deionized water, and the mixture was stirred at room temperature and stirred at 300 r / min for 3 h to obtain a mixed solution A;
[0065] (2) 1.50 g of nickel nitrate hexahydrate and 0.30 g of lanthanum nitrate hexahydrate were added into 10 mL of deionized water and ultrasonically dispersed for 10 min to obtain a mixed solution B;
[0066] (3) Adding mixed solution B to mixed solution A, stirring at 50° C. and 350 r / min for 12 h to obtain mixed solution C;
[0067] (4) After stirring, the mixed solution C is centrifuged and dried, and the obtained product is calcined in a muffle furnace at 650° C. for 5 h to obtain a solid base catalyst loaded with nickel oxide and lanthanum oxide.
[0068] The mass ratio of the carrier halloysite to the active component in the catalyst is 1:0.5, and the mass ratio of nickel oxide to lanthanum oxide in the active component is 1:0.3; it is detected that the particle size range of the nickel oxide loaded on the carrier is 10-30nm, and the particle size range of the lanthanum oxide is 50-100nm.
[0069] Comparative Example 1
[0070] The steps for preparing the solid base catalyst are the same as those in Example 1, except that in step (2), only nickel nitrate hexahydrate is added instead of lanthanum nitrate hexahydrate, and the active component in the prepared catalyst is only nickel oxide, and the remaining steps are the same. It is found that the nickel oxide particles loaded on the carrier are agglomerated, and the particle size range of the active component particles is 100nm to 1μm.
[0071] Comparative Example 2
[0072] The steps for preparing the solid base catalyst are the same as those in Example 1, except that in step (2), 1.15 g of nickel nitrate hexahydrate and 0.55 g of lanthanum nitrate hexahydrate are added to 10 mL of deionized water, and ultrasonic dispersion is performed for 10 min to obtain a mixed solution B, and the remaining steps are the same. The mass ratio of nickel oxide to lanthanum oxide in the catalyst active component is 1:0.7. It is detected that the particles of the active component loaded on the carrier are severely agglomerated, and the particle size range of the active component particles is 500 nm to 2 μm.
[0073] Comparative Example 3
[0074] The steps for preparing the solid base catalyst are the same as those in Example 1, except that in step (2), 1.03 g of nickel nitrate hexahydrate and 0.63 g of lanthanum nitrate hexahydrate are added to 10 mL of deionized water, and ultrasonic dispersion is performed for 10 min to obtain a mixed solution B, and the remaining steps are the same. The mass ratio of nickel oxide to lanthanum oxide in the catalyst active component is 1:0.9; the particles of the active component loaded on the carrier are severely agglomerated, and the particle size range of the active component particles is 500 nm to 10 μm.
[0075] Comparative Example 4
[0076] Commercially available nano nickel oxide with a particle size range of 10 to 30 nm is directly used as a solid base catalyst without any carrier.
[0077] Example 7 Catalyst Performance Evaluation
[0078] The catalysts obtained in Examples 1-6 and Comparative Examples 1-4 were used to prepare biodiesel. The specific steps are as follows:
[0079] (1) Adding raw oil and methanol in a mass ratio of 1:(7-9) into a reaction kettle, stirring and heating to 70-90°C;
[0080] (2) Add the prepared catalyst into a reaction kettle, with the mass ratio of the catalyst to the raw oil being 2% to 3%, and react for 4 to 6 hours to prepare biodiesel.
[0081] After the reaction is completed, excess methanol is recovered and the solid catalyst is separated and recovered to obtain a biodiesel product. The biodiesel yield is analyzed and tested. The reaction conditions and product yields for each catalyst performance evaluation are shown in Table 1 below.
[0082] Table 1 Catalyst performance evaluation reaction conditions and yields of Examples and Comparative Examples
[0083] Mass ratio of raw oil and methanol Catalyst dosage Reaction temperature Reaction time Yield Example 1 1:9 2.5% 80℃ 5h 97.4% Example 2 1:7 3% 70℃ 5h 97.7% Example 3 1:8 3% 90℃ 4h 98.5% Example 4 1:9 2% 70℃ 6h 98.3% Example 5 1:9 2.5% 80℃ 5h 97.9% Example 6 1:9 2.5% 80℃ 5h 98.6% Comparative Example 1 1:9 2.5% 80℃ 5h 93.6% Comparative Example 2 1:9 2.5% 80℃ 5h 90.5% Comparative Example 3 1:9 2.5% 80℃ 5h 88.9% Comparative Example 4 1:9 2.5% 80℃ 5h 89.2%
[0084] It can be seen from the data in the above table that the solid base catalyst provided by the present invention has a yield higher than 97.4% in the reaction for preparing biodiesel under the condition of lower catalyst dosage. Under the same biodiesel preparation reaction conditions, the yield is higher than that of the comparative example, indicating that the solid base catalyst provided by the present invention has high catalytic activity in the reaction for preparing biodiesel.
[0085] The nano nickel oxide in Comparative Example 4 is used as a catalyst without any carrier. Since the pure nickel oxide particles are easy to agglomerate in the reaction system of biodiesel, it is easy to cause uneven dispersion, resulting in a relatively low yield of the product, and it is easy to lose during use and difficult to recover. In Comparative Example 1, when the nano nickel oxide is used as a carrier of halloysite, due to the spiral tubular well-developed pore structure of the purified halloysite, the loading of the active component nano nickel oxide is more uniform than that of Comparative Example 4, and the yield of the product is improved to a certain extent. The solid base catalyst with nano nickel oxide and lanthanum oxide as active components provided by the present invention, due to the addition of a certain proportion of lanthanum oxide component on the basis of Comparative Example 1, is conducive to further dispersion of the active component nano nickel oxide on halloysite, so that the yield of the product can reach more than 97.4%, realizing efficient production. However, when the proportion of lanthanum oxide component is further increased, it is easy to cause more obvious agglomeration between particles of the active component, affecting the yield of the biodiesel product.
[0086] Example 8 Catalytic Lifetime Evaluation
[0087] After the solid base catalysts prepared in Example 6 and Comparative Example 1 were used to produce biodiesel under the reaction conditions described in Example 7, the separated and recovered solid base catalysts were washed three times with anhydrous ethanol, dried in an oven at 80°C, and recycled for the next batch of reactions. The yield of biodiesel was used as an indicator, and the performance of the catalytic life was shown in Table 2.
[0088] Table 2 Batch recycling biodiesel yield
[0089] Example 6 Comparative Example 1 Batch 1 98.6% 93.6% Batch 2 98.1% 92.5% Batch 3 97.8% 91.2% Batch 4 97.5% 89.8% Batch 5 97.3% 88.4% Batch 6 97.0% 87.0% Batch 7 96.6% 85.6% Batch 8 96.1% 84.0% Batch 9 95.5% 82.5% Batch 10 94.2% 80.1%
[0090] According to the continuous decrease in yield data, it can be seen that the catalytic activity of the solid catalyst decreases with the increase in the reaction batches, but the solid base catalyst loaded with nano nickel oxide provided by the present invention can still achieve a yield of more than 94.2% after 10 repeated reactions, and has excellent reusability and long service life; when the active component is only nano nickel oxide, the yield is significantly reduced, and the yield is reduced to 80.1% after 10 repeated reactions. Due to the addition of nano lanthanum oxide in the active component, the composite oxide solid base catalyst of the present invention has significant advantages in catalyst reuse and service life.
Claims
1. Application of a composite oxide solid base catalyst in the preparation of biodiesel, characterized in that: The solid base catalyst uses halloysite as a carrier to load active components; the active components include nano nickel oxide and nano lanthanum oxide; The mass ratio of the carrier halloysite to the active component is 1:(0.5-1), and the mass ratio of the nano nickel oxide to the nano lanthanum oxide in the active component is 1:(0.1-0.5).
2. The use of the solid base catalyst according to claim 1 in the preparation of biodiesel, characterized in that: The mass ratio of the nano nickel oxide to the nano lanthanum oxide in the active component is 1:(0.3-0.5).
3. The use of the solid base catalyst according to claim 1 in the preparation of biodiesel, characterized in that: The particle size of the nano nickel oxide is 10-30 nm; the particle size of the nano lanthanum oxide is 50-100 nm.
4. The use of the solid base catalyst according to claim 1 in the preparation of biodiesel, characterized in that: The preparation method of the solid base catalyst specifically comprises the following steps: (1) purifying halloysite powder and adding it into water to obtain a mixed solution A; (2) mixing the nickel nitrate and lanthanum nitrate solutions to obtain a mixed solution B; (3) Mixing the mixed solution A and the mixed solution B, stirring at 50-70 °C for 6-12 h, and obtaining a mixed solution C; (4) The mixed solution C is centrifuged and dried, and the obtained product is calcined and activated to obtain a solid base catalyst loaded with nano-nickel oxide and nano-lanthanum oxide.
5. The use of the solid base catalyst in the preparation of biodiesel according to claim 4, characterized in that: In the step (1), the purification of the halloysite powder comprises the following steps: The halloysite powder is immersed in a 0.5-1 mol / L dilute nitric acid solution, the mixing ratio of the halloysite powder and the dilute nitric acid solution is 30-80 g / L, and mixed at 60-90 °C for 6-12 hours, filtered, washed, dried, and calcined at 350-450 °C for 2-5 hours to obtain a purified halloysite powder.
6. The use of the solid base catalyst in the preparation of biodiesel according to claim 4, characterized in that: In the step (1), the purified halloysite powder is added to water and stirred at 300-400 r / min for 2-4 h to obtain a mixed solution A; in the step (2), the nickel nitrate and lanthanum nitrate solutions are mixed and ultrasonically dispersed for 10-20 min to obtain a mixed solution B.
7. The use of the solid base catalyst in the preparation of biodiesel according to claim 4, characterized in that: In the step (3), the stirring speed of the mixed solution A and the mixed solution B is 350-450 r / min.
8. The use of the solid base catalyst in the preparation of biodiesel according to claim 4, characterized in that: In the step (4), the product obtained by separation and drying is calcined in a muffle furnace at 650-850° C. for 2-5 h to activate the solid base catalyst loaded with nano-nickel oxide and nano-lanthanum oxide.
9. The use of the solid base catalyst in the preparation of biodiesel according to claim 1, characterized in that: The specific steps include: (1) Add raw oil and methanol into the reactor at a mass ratio of 1:(7-9), stir and heat to 70-90 °C; (2) Add the solid base catalyst into the reaction kettle, the mass ratio of the solid base catalyst to the raw oil being 2% to 3%, and react for 4 to 6 hours to prepare biodiesel.
Citation Information
Patent Citations
Preparation method of La-nano PO43- / ZrO2 solid acid catalyst for producing biodiesel
AU2020102722A4
Hydrogenation catalyst for coal tar and ethylene tar and preparation method thereof
CN102886274A
Preparation method for preparing biological aviation kerosene ultra-dispersed hydrodeoxygenation and hydroisomerization catalysts from castor oil
CN104815697A
Acidic-basic solid catalyst, preparation and application thereof in production of biodiesel
CN110665488A
Solid catalyst and preparation method and application thereof
CN111921531A
